On the Difficulty of Refuting or Confirming the Arguments about the Caste System - Dunkin Jalki; Sufiya Pathan (Theatrum Historiae)
Any attempt to understand Indian society through the scholarship on caste confronts us with a large number of problems. Scholars of the last 150 years have routinely observed and even criticised writings on caste for these problems. Such criticisms, however, have neither led us towards a confirmation nor the abandonment of the so-called caste theories. How do we explain this curious fact? Caste scholars hold the complexity of the issue as responsible for the lack of a robust theory of the caste system. Hence, they set out to collect more facts in order to buttress the theory. More facts, however, create more problems. It is not only the quest for more data, which is expected to save the ‘theories’ of the caste system, but also a struggle to match the thus collected field data with the claims about the caste system that unites the colonial and modern writers on the caste system. This paper suggests that the failure of caste scholars to account for field data is not a result of the complexity of the field, but rather an outcome of the kind of entity that the ‘caste system’ is. The so-called caste system is an experiential entity of the West, which can neither be confirmed nor refuted by using empirical facts from India. Any attempt to do so will only generate unproductive debates.